Effect of Hesperetin on Isoprenaline-induced Hypertrophy of H9C2 Cardiomyocytes: Effect of Hesperetin on Hypertrophy of H9C2 Cardiomyocytes - Liu, Bo; Qiu, Beilei; Zhang, Suchuan (Cellular and Molecular Biology, 2022)
An experiment was carried out to investigate the effect of hesperetin on isoproterenol-induced H9C2 cardiomyocyte hypertrophy and its possible mechanism. For this aim, H9C2 cardiomyocytes were coincubated with different concentrations of hesperetin (0.125, 0.25, 0.5, 1μmol/L) and isoproterenol to detect the changes in the area of H9C2 cells, the expression of cardiac hypertrophy marker β-MHC mRNA and autophagy marker LC3II; H9C2 cells were coincubated with hesperetin and isoproterenol at the optimal intervention concentration, and the intervention time was set to 6h, 12h, 24h, respectively, and the changes of H9C2 cell area, β-MHC mRNA and LC3II expression were detected. Results showed that hesperetin could reduce isoproterenol-induced H9C2 cardiomyocyte area enlargement; hesperetin can reduce β-MHC mRNA expression in isoproterenol-induced H9C2 cardiomyocyte; hesperetin can increase the expression level of LC3II in isoproterenol-induced H9C2 cardiomyocyte. Conclusion Hesperetin may improve the hypertrophy of H9C2 cardiomyocytes induced by isoproterenol by activating autophagy.